2013
DOI: 10.2174/13816128113199990493
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Drug Resistance in Cancer Chemotherapy: Coordinated Role and Regulation of Efflux Transporters and Metabolizing Enzymes

Abstract: Cancer remains one of the major leading causes of death worldwide. Acquisition of multidrug resistance (MDR) remains a major impediment to successful chemotherapy. As the name implies, MDR is not limited only to one drug but often associated to structurally and functionally unrelated chemotherapeutics. Extensive research and investigations have identified several mechanisms underlying the development of MDR. This process of drug resistance is considered to be multifactorial including decreased drug accumulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(70 citation statements)
references
References 0 publications
1
64
0
5
Order By: Relevance
“…Currently, the screening of agents inducing chemosensitivity is the main method to overcome this problem (20). In the present study, JNK pathway inhibition was shown to cause cytotoxicity on NPC cells, indicating that this signaling pathway exerts a growth promotion function in NPC cells.…”
Section: Discussionsupporting
confidence: 48%
“…Currently, the screening of agents inducing chemosensitivity is the main method to overcome this problem (20). In the present study, JNK pathway inhibition was shown to cause cytotoxicity on NPC cells, indicating that this signaling pathway exerts a growth promotion function in NPC cells.…”
Section: Discussionsupporting
confidence: 48%
“…As a consequence of efflux, drug absorption is reduced and bioavailability of xenobiotics diminishes at the target tumor tissue. In recent reviews we have elaborately discussed the role of these efflux transporters in drug resistance [342]. A list of anticancer agents that are substrate for various efflux transporters is presented in Table 4.…”
Section: Chemotherapy and Drug Resistancementioning
confidence: 99%
“…Our laboratory has examined the strategy of combining ritonavir-a retroviral protease inhibitors with anticancer drugs to control drug efflux, and metabolism thereby allowing sufficient drug entry into tumor cells [342]. Vinblastine mediated induction of efflux transporters (MDR1, MRP2), metabolizing enzyme (CYP3A4) and nuclear receptor (PXR) is reversed in the presence of ritonavir in human colon adenocarcinoma cells (LS-180).…”
Section: Chemotherapy and Drug Resistancementioning
confidence: 99%
“…[44] However, traditional anticancer drugs usually suffered from a number of drawbacks, [45,46] such as the poor specificity and severe side effects. In recent decades, drug resistance has also emerged as a great challenge, [47,48] and has become one of the major sources of the failure in clinical cancer treatments. DNA nanostructures are acting as one of the prominent anti-cancer drug vehicles because of a variety of intriguing structural and chemical features, such as complexity-controlled self-assembly, intricate and programmed shapes, suitable sizes and biocompatibility, and more interestingly the structural tenability.…”
Section: Small-molecular Drugsmentioning
confidence: 99%